1991
DOI: 10.1089/jop.1991.7.285
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Hypotensive Effects of Medetomidine and Its Analogs

Abstract: The ocular hypotensive effects of medetomidine, a relatively selective (X2-agonist, and its analogs were tested in rabbits and cats and their inhibition of adenylate cyclase in the isolated bovine ciliary process was also studied. It was found that topical unilateral administration of medetomidine (0.5-2.0%) to the normotensive rabbits produced a dose-dependent bilateral decrease in IOP with peak reduction in IOP at 2 hr in the treated eye and 1 hr in the untreated eye. A dose-dependent mydriasis was also obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Peripheral a-2 receptors in the eye, both prejunctionally on ocular sympathetic nerve fibres and postjunctionally, are potentially involved in the physiological regulation of IOP. This regulation is achieved by decreasing the stimulated production of cyclic AMP in the ciliary process (4,5). To our knowledge, the effect of medetomidine on the IOP and pupil diameter of the canine eye has not been described previously.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Peripheral a-2 receptors in the eye, both prejunctionally on ocular sympathetic nerve fibres and postjunctionally, are potentially involved in the physiological regulation of IOP. This regulation is achieved by decreasing the stimulated production of cyclic AMP in the ciliary process (4,5). To our knowledge, the effect of medetomidine on the IOP and pupil diameter of the canine eye has not been described previously.…”
Section: Introductionmentioning
confidence: 90%
“…MedeDepartment of Clinical Sciences of Companion Animals, Faculty of Veterinary tomidine is commonly used to sedate animals for non-surgical interventions, such as oral inspection or radiography or as a premedication before general anaesthesia. Studies of normotensive rabbits and cats have demonstrated that medetomidine lowers the IOP after its topical application to the eye (4,5). Peripheral a-2 receptors in the eye, both prejunctionally on ocular sympathetic nerve fibres and postjunctionally, are potentially involved in the physiological regulation of IOP.…”
Section: Introductionmentioning
confidence: 99%
“…5, 9 and 10 mmHg) with no initial transient hypertension, an effect previously observed following topical ipsilateral applications of certain a 2 / imidazoline agonists (I 1 ) to eyes of light-adapted rabbits (Burke and Potter, 1986;Jin et al, 1991;Potter and Ogidigben, 1991;Ogidigben et al, 1994). The lack of an initial hypertensive response to naphazoline could be due to the fact that the intraocular pressure and sympathetic tone of dark-adapted rabbits are elevated compared to light-adapted rabbits (McLaren, Brubaker and FitzSimon, 1996).…”
mentioning
confidence: 64%
“…Many drugs activate the adenyl cyclase in the ciliary process leading to an accelerated rate of production of intracellular cAMP and aqueous humor formation (33). In glaucoma treatment, many b-blockers also exert their ocular hypotensive action through inhibition of cAMP production in ciliary epithelium and aqueous humor formation (18,34).…”
Section: Discussionmentioning
confidence: 99%